Program Tahfidzul Qur’an untuk Membentuk Karakter Religius di MAN Sidoarjo - Yunusi, Muhammad Yusron Maulana El; Firdaus, Kharisma Syifanaya; Abror, Sirojuddin (Yayasan Kawanad, 2025)
The Tahfidzul Qur’an program at MAN Sidoarjo serves as a strategic effort to shape students’ religious character by reinforcing Qur’anic values in their daily lives. This study employed the Participatory Action Research (PAR) method, involving tahfidz teachers, students, and researchers collaboratively through stages of planning, action, observation, and reflection. The research involved 20 purposively selected tahfidz students. Data were collected through observation, interviews, religiosity questionnaires, and documentation, and analyzed using qualitative descriptive techniques.The findings indicate a significant improvement in students’ religious character, with the average religiosity score increasing from 2.76 to 3.81, a gain of 1.05 points. Positive changes were observed in prayer discipline, honesty, responsibility, and social awareness. The tahfidz program not only enhanced memorization skills but also fostered spiritual awareness, moral integrity, and self-control. The school’s religious environment played an essential role in strengthening the internalization of Qur’anic values. Therefore, the Tahfidzul Qur’an program can be considered a sustainable model for character development in Islamic educational institutions.